Technological Innovations in Agronomic Iron Biofortification: A Review of Rice and Bean Production Systems in Brazil - Caroline Figueiredo Oliveira; Thaynara Garcez da Silva; Estefani Kariane Oliveira; Fabíola Lucini; Elcio Ferreira Santos (AgriEngineering)
Iron deficiency is a widespread public health concern, particularly in regions where rice (Oryza sativa) and beans (Phaseolus spp.) are staple foods with naturally low bioavailable iron content. Agronomic biofortification is a practical strategy to increase micronutrient levels in crops through soil, foliar, and seed-based fertilization techniques. This review synthesizes scientific studies published between 2014 and 2024 that evaluated the effectiveness of agronomic iron biofortification methods in rice and beans. The results demonstrate that site-specific interventions, such as the selection of iron sources and application methods, can improve iron concentration in grains and contribute to more nutritious and resilient food systems. However, challenges remain. There is limited information about human iron bioavailability, and the response to fertilization varies depending on soil and environmental conditions. To address these gaps, future research should include bioavailability assessments and field validation. Even so, integrating iron biofortification into standard fertilization practices is a promising approach to improve food quality and combat hidden hunger in vulnerable populations.